Preparation and characterization of crosslinked electrospun pullulan nanofiber membrane as a potential for biomaterials. Issue 6 (3rd June 2018) - Li, Yafang; Ma, Xiaomin; Ju, Jingge; Sun, Xiaobin; Deng, Nanping; Li, Zongjie; Kang, Weimin; Cheng, Bowen
Abstract: Pullulan nanofiber membrane (Pull-NM) was prepared by electrospinning method and its stability in the water was improved by a chemical crosslinking with mixed solution of ethylene glycol diglycidyl ether (EGDE) and ethanol absolute as crosslinking agent. The effect of crosslinked pullulan nanofiber membrane (C-l-Pull-NM) with different process conditions was studied and the excellent crosslinking reaction condition is proved to be 1:70 (EGDE: ethanol absolute) for 24 h. The analytical methods, including SEM, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, and differential scanning calorimetry, were used to study morphology, structure, and thermal performance of the nanofiber membrane. In addition, the swelling behavior and tensile were also discussed. The results showed that the water resistance of crosslinked nanofiber membrane had a significant improvement. Furthermore, the maximum water absorption and the strength were reached to about 520 and 192.7%, respectively.